Multi-heteroatom-doped porous carbon electrodes from 3D printing and conformal carbonization of ionic liquids for electrocatalytic CO2 conversion into syngas - Wei Wang; Na Zhao; Kai Zhao; Miao Zhang; Kanglei Pang; Yu Zhang; Jiayin Yuan (Communications Chemistry)
Abstract 3D printing as an advanced manufacturing technique provides an alternative cost-effective option for design and preparation of porous catalytic electrodes. Herein, carbonaceous catalytic electrodes with ternary dopants of boron (B), phosphorous (P), and nitrogen (N) (termed BPN-3Dp-CCEs) were successfully engineered via combination of the 3D printing technique and the following conformal carbonization of ionic liquid. The as-made electrodes were in turn applied to electrify CO2 into syngas in a controllable composition of a H2:CO molar ratio of 0.32–3.46. Notably, the BPN-3Dp-CCEs have tailored 3D macroscopic shapes of self-supporting skeletons, and due to ternary doping, demonstrated promoted catalytic activity in the electrocatalytic CO2 conversion into syngas. Upon optimization, the electrode remained stable in structure and performance after 10 h of a continuous CO2 electrolysis operation. This study casts insights and fuels the continuous exploration of multi-heteroatoms doped porous carbon electrodes for metal-free catalytic applications.